2007
DOI: 10.1103/physreva.75.023619
|View full text |Cite
|
Sign up to set email alerts
|

Bose-Einstein-condensed systems in random potentials

Abstract: The properties of systems with Bose-Einstein condensate in external time-independent random potentials are investigated in the frame of a self-consistent stochastic meanfield approximation. General considerations are presented, which are valid for finite temperatures, arbitrary strengths of the interaction potential, and for arbitrarily strong disorder potentials. The special case of a spatially uncorrelated random field is then treated in more detail. It is shown that the system consists of three components, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
158
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(173 citation statements)
references
References 47 publications
9
158
0
6
Order By: Relevance
“…Inserting (42), (43) into (36), (37) and using the Schwinger integral (46), [53, (3.471.9)], and [53, (8.469.3)], as well as performing the replica limit N → 0 yields:…”
Section: Free Energymentioning
confidence: 99%
See 1 more Smart Citation
“…Inserting (42), (43) into (36), (37) and using the Schwinger integral (46), [53, (3.471.9)], and [53, (8.469.3)], as well as performing the replica limit N → 0 yields:…”
Section: Free Energymentioning
confidence: 99%
“…A major result is that increase in the disorder strength at zero temperature yields a first-order quantum phase transition from a superfluid to a Bose-glass phase, where in the latter all particles reside in the respective minima of the random potential. This prediction is achieved for three dimensions by solving the underlying Gross-Pitaevskii equation with a random phase approximation [36], as well as by a stochastic self-consistent mean-field approach using two chemical potentials, one for the condensate and one for the excited particles [37,38]. Dual to that, the non-perturbative approach of Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increasing the disorder strength at small temperatures yields a first-order quantum phase transition from a superfluid to a Bose-glass phase, where in the latter case all particles reside in the respective minima of the random potential. This prediction is achieved at zero temperature by solving the underlying Gross-Pitaevskii equation with a random phase approximation [36], as well as at finite temperature by a stochastic self-consistent meanfield approach using two chemical potentials, one for the condensate and one for the excited particles [37]. Numerically, Monte-Carlo (MC) simulations have been applied to study the homogeneous dirty boson problem.…”
Section: Introductionmentioning
confidence: 99%
“…In presence of random on-site energies, T c increases for large filling, but much less than for for bond-disordered lattices, resulting in very small shift of T c for small disorder. These results should be compared with the findings for a continuous (i.e., without optical lattice) Bose gas in presence of a disordering potential [32,33,34,35,36]: without any confining potential, it has been shown that the critical temperature decreases with disorder [32]. In Refs.…”
Section: Introductionmentioning
confidence: 99%